Endovascular salvage of non-maturing autogenous arteriovenous fistulas by using angioplasty and competitive vein embolization. Issue 5 (September 2020) - Nauta, Lisette; Voorzaat, Bram M; Rotmans, Joris I; Ghariq, Elyas; Urlings, Thijs; van der Bogt, Koen E A; van der Linden, Edwin
Introduction: The aim of this study is to evaluate the maturation and patency rates after endovascular treatment of non-maturing arteriovenous fistulas with percutaneous transluminal angioplasty, embolization of competitive veins, or a combination of both in a series of consecutive patients. Material and methods: Retrospective evaluation of patients with non-matured arteriovenous fistulas treated in our hospital was performed. Fistulography and ultrasonography was performed in all patients to evaluate the presence of stenosis and competitive veins. Significant stenoses (> 50%) were treated with balloon angioplasty and competitive veins (accessory and collateral veins) with coil embolization. Results: A total of 78 fistulas were treated. Angioplasty and coil embolization were performed in 73 and 51 patients, respectively. No major complications occurred. In 65 out of 78 arteriovenous fistulas (83%), successful cannulation with two needles was possible after endovascular treatment. Sixty-three arteriovenous fistulas (81%) were used successfully for at least 3 months. Accessory veins were the only lesion present in 14% of the arteriovenous fistulas; coil embolization of these accessory veins resulted in 100% successful maturation. The estimated 3, 6, and 12 months postintervention assisted primary patency rates were, respectively, 73%, 55%, and 45%. The estimated 3, 6, and 12 months postintervention secondary patency rates were, respectively, 81%, 78%, and 73%. Conclusion and discussion: Angioplasty and coil embolization are successful and safe procedures that can convert a non-mature fistula into a mature one in more than 80% of patients. Accessory vein embolization may be more important than collateral vein embolization in the presence of stenosis.